EFEKTIVITAS LEARNING MANAGEMENT PADA DIKLAT TEKNIS SUBSTANTIF PKG DAN PKB BAGI GURU MADRASAH DI LINGKUNGAN BALAI DIKLAT KEAGAMAAN BANDUNG TAHUN 2018 - Mohamad Fauzan (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
This research aims to explain the effectiveness of learning management and obstacle of PKG and PKB training for Madrasah 'Aliyah teachers at the Bandung Religious Education and Training Center in 2018. The research is descriptive using observation and interview technique of data collection. Data was analyzed by qualitative data analysis techniques through three stages namely data reduction, display, and verification. The results of this study revealed that the education and training process is effective with the final average score of all indicators of 88.53 (very good). The obstacles found during the training management process lie in the management of the training material and the management of the leaning organization. The research recommends touse a variety of learning methods through grouping training participants and collaboration in working on the worksheets.